(Re)Defining Airport Experience: A New Framework Proposition - Yerimou, Pantelitsa; Themistocleous, Christos (My University, 2024)
This chapter investigates the airports’ transformation into dynamic commercial servicescapes and their profound effects on travelers' emotions and underlying behaviors. We examine how feelings influence overall satisfaction, airport revisit intentions, and the likelihood of favorable word-of-mouth. Emphasis is given on previously underexplored concepts that impact travelers’ experiences with a particular focus on sense of place, environmental responsiveness, and human-related factors. Following the review of relevant studies and theories, a new conceptual framework is proposed offering a new perspective for airport servicescape analysis and its impact on traveler behavior. Finally, we provide a review of how advances in technology and psychological stimuli within the environment attempt to mitigate managerial uncertainty and enhance behavioral intention forecasts within a given airport setting.
Keywords: Airport experience; Emotions; Revisit; WoM